2021
DOI: 10.1177/23800844211035669
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Unmet Dental Health Needs in US Adults in 2018: A Cross-Sectional Analysis

Abstract: Objective: To identify predictors of unmet dental needs for adults 18 y of age or older in the United States. Method: Using the Aday and Andersen framework and data from the 2018 Behavioral Risk Factor Surveillance System (BRFSS), we ran logistic regression to estimate predictors for adults of not having a dental visit within 5 y and having lost any teeth using a national sample of 155,060 survey respondents. Results: Results showed that predisposing factors (age, race/ethnicity, gender, and educational attain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…A previous study reported several predictors of unmet dental need among adults in the United States (5). Therefore, the decline in dental visits between 2019 and 2020 may be attributable to other factors in addition to the impact of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…A previous study reported several predictors of unmet dental need among adults in the United States (5). Therefore, the decline in dental visits between 2019 and 2020 may be attributable to other factors in addition to the impact of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 95%
“…Significantly different from non-Hispanic Asian adults for both 2019 and 2020 (p < 0.05) 4. Significantly different from non-Hispanic Black adults for both 2019 and 2020 (p < 0.05) 5. Significantly different from non-Hispanic other and multiple race adults for both 2019 and 2020 (p < 0.05).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Low coverage of oral care remains a global problem affecting also high‐income countries 2 . Additionally, social inequities in oral health and care are consistently reported in several high‐income countries, even in Nordic countries where the financing and delivery of oral care are known to be a public responsibility 3–7 …”
Section: Introductionmentioning
confidence: 99%
“…Beyond pregnancy, Gaskin et al (2022) describe predictors for unmet dental needs in >150,000 US adults, resulting from their analyses of the 2018 Behavioral Risk Factor Surveillance System. In addition to finding that predisposing and enabling factors predicted tooth loss, their results demonstrate that differences in unmet dental needs are modulated by the vitality of each state’s oral health policy, indicating that improvements in state and federal oral health programs could vastly improve oral health.…”
mentioning
confidence: 99%